Genome‐wide association analysis for response of Senegalese sorghum accessions to Texas isolates of anthracnose. Issue 2 (26th April 2021) - Ahn, Ezekiel; Prom, Louis K.; Hu, Zhenbin; Odvody, Gary; Magill, Clint
Abstract: Anthracnose disease of sorghum is caused by Colletotrichum sublineola, a filamentous fungus. The genetic basis of resistance to anthracnose in sorghum is largely unclear, especially in Senegalese sorghum germplasm. In this study, 163 Senegalese sorghum accessions were evaluated for response to C . sublineola, and a genome‐wide association study (GWAS) was performed to identify genetic variation associated with response to C. sublineola using 193, 727 single nucleotide polymorphisms (SNPs) throughout the genome. Germplasm diversity analysis showed low genetic diversity and slow linkage disequilibrium (LD) decay among the Senegalese accessions. Phenotypic analysis resulted in relatively low differences to C. sublineola among the tested population. Genome‐wide association study did not identify any significant association based on a strict threshold for the number of SNPs available. However, individual analysis of the top eight SNPs associated with relative susceptibility and resistance identified candidate genes that have been shown to play important roles in plant stress tolerance in previous studies. This study identifies sorghum genes whose annotated properties have known roles in host defense and thus identify them as candidates for use in breeding for resistance to anthracnose. Core Ideas: A total of 163 Senegalese sorghum accessions were evaluated for response to C. sublineola . A genome‐wide association study was performed to identify genetic variation associated with response to C. sublineola . Top single‐nucleotide polymorphisms were associated with genes known to contribute to defense responses.